A nuclear magnetic resonance spectroscopy study of the solvent dependence of the barrier to rotation in N,N,N',N'-Tetramethylthiodicarbonic diamide : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Hughes, Lesley Marion (Massey University, 1977)
Barriers to rotation were determined from variable-temperature nuclear magnetic resonance spectra. The computer program used to calculate the rotational rates was validated by obtaining results in good agreement with the literature values from studies carried out on neat N,N-dimethylcarbamic chloride. The barrier to rotation for N,N,N',N'-tetramethylthiodicarbonic diamide was measured in a variety of solvents and large variations in activation energy were observed (more than 40 kJ mol -1 ). The free energies could be correlated with the dielectric constant, the dipole moment, the Hildebrand solubility parameter and the empirical polarity parameters E T and Z. A linear plot of ΔH ≠ 298 versus ΔS ≠ 298 different solvents was obtained. Attempts to obtain other systems suitable for NMR study are reported.
Keywords: Nuclear magnetic resonance spectroscopy